A Comparative Study of Teachers’ Self-Efficacy for Teaching Stem Subjects and Attitudes Toward Stem Education According to Gender at Wattana Wittaya Academy, Bangkok, Thailand - Sachdev, Sunita; Eamoraphan, Suwattana (Scholar: Human Sciences, 2021)
The purpose of conducting this research was to determine the level of teachers’ self-efficacy when teaching STEM subjects and their attitudes towards STEM education at Wattana Wittaya Academy in Bangkok, Thailand. A second purpose was to determine whether there was a significant difference in teachers’ self-efficacy for teaching STEM subjects and attitudes toward STEM education according to gender. As a source of data collection, the researcher used Teachers’ Self-Efficacy for Teaching STEM Subjects and Attitudes Toward STEM Education (T-STEM Questionnaire). The respondents were 67 teachers completed the questionnaire. The data obtained were analyzed by descriptive statistics, means and standard deviations and independent samples t-test. The findings of this study were as follows: Teachers had a high level of self-efficacy for teaching STEM subjects. Teachers had positive attitudes toward STEM education. There was no statistical difference between teachers’ STEM teaching self-efficacy for teaching STEM subjects and attitudes toward STEM education according to gender at Wattana Wittaya Academy, Bangkok, Thailand. Recommendations for practice and future research are provided.